Is integration of ethics in Islam with social sciences viable? exploring the meaning and nature of al-akhlaq from the Quranic and Muslim ethicists' perspectives = Adakah integrasi ilmu etika dalam Islam dengan sains kemasyarakatan berdaya maju? eksplorasi makna dan ciri-ciri al-Akhlaq dari perspektif al-Qur’an dan pakar ilmu etika Muslim - Awang Abd. Rahman @ Jusoh, Amilah (IIUM Press, International Islamic University Malaysia, 2018)
Akhlaq is not only a major dimension of Islam, but also the root of humanity in Islam. However, its relevance to the modern disciplines is yet to be extensively explored. This paper aims at looking into the relevance of akhlaq to the modern life, mainly through the Social Science disciplines. This paper analyzes the meaning of akhlaq with special connotation and expectation from the Qur’anic perspective, and its interpretation from Muslim ethicists. This paper seeks to answer the central problem related to typical perception on religious ethics that hinders its harmonious integration into the realm of human experience. The paper touches the issues on the real nature of Akhlaq and the place of human freedom and objectivity in Akhlaq. The role of Akhlaq in dealing with individual versus societal end is also explored. It is found that Akhlaq acts beyond the typical normative ethics and consistent in its standpoint of human agency with its concepts of motivation and sanction as addressed by the Qur’an. Instead of being abstract and dry, the generic nature of values in Akhlaq is adjustable to different experience, and harmonious to the life needs both at individual as well as societal level of man. Hence, akhlaq opens its door widely to work together with Social Science disciplines which can further enhance a better understanding of humanities in facing the social changes.